Psychological Abuse in Spanish Same-Sex Couples: Prevalence and Relationship Between Victims and Perpetrators - Barrientos-Delgado, J (Routledge, 2018)
This study investigates the prevalence of psychological abuse victimization in same-sex couples and the relationship between being a victim and a perpetrator of these negative behaviours. The final sample consisted of 107 adults residing in Spain who identified themselves as lesbian women and gay men, and who had been involved in a conflictive same-sex relationship. Participants were asked how frequently they would label their experience of psychological abuse and three different estimation methods were used. Furthermore, the relationship between being a victim and being a perpetrator of psychological abuse behaviours was calculated through the behavioural estimation method using a questionnaire. The results showed that the prevalence rates varied from 11.3% to 56.6%, depending on the estimation method, and they revealed that there was no correlation between receiving and enacting psychological abuse behaviours. The variation in prevalence rates highlights methodological differences that limit the extent to which comparisons can be made across studies. Three estimation methods are introduced to stimulate future research on this issue. © 2017 The European Association for the Advancement of the Social Sciences.